ANALISA PERENCANAAN TEKNIS PERHITUNGAN STRUKTUR KOLOM PADA PROYEK APARTEMEN SILKTOWN ALEKSANDRIA TOWER - Ihwanudin, Irfan (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2019)
The Alexandria Town Silk Tower apartment project is one of the apartment projects in the city to meet the megapolitan community's need for residential homes. With the construction of vertical dwellings such as apartments, there will be a lot of use of column structures. Therefore, it is necessary to analyze the technical planning of the column structure in the Silktown Alekandria Tower apartment project which aims to obtain shear moments and forces and can determine the reinforcement that must be used, as well as checking whether the column column included in the short column or long column and the column structure must be in accordance with SNI for safe columns for building structures. Analysis of column structures is carried out using SAP2000. The results of the analysis using SAP2000 obtained value of loading W = 1775.56 kg. Reinforcement in Column K2-1 with dimensions 800 x 1500 and Concrete Quality Fc 35 Mpa value d = 1446. Calculation of longitudinal, Asperia = 22500 mm2, n (number of reinforcement) = 45,928,304 mm-. The stirring shear force held Vs = 3.08, reinforcement of Av shear, u 1232.5166 mm, stirring distance = 215.2749873, the distance chosen after controlling is 200 d22.